Social recovery: A neglected dimension of caring for women with perineal trauma in Iran - Nahid Jahani Shoorab; Ali Taghipour; Masoumeh Mirteimouri; Robab Latifnejad Roudsari (Wolters Kluwer Medknow Publications, 2020)
Background: Social recovery during the postnatal period in women with perineal trauma is a little-known concept. Therefore, this study was designed to explore the experiences of social recovery in women with childbirth-related perineal trauma. Materials and Methods: A qualitative approach using content analysis was adopted to study a purposive sample of 22 postnatal women with perineal trauma during birth at Omol-banin Hospital, Mashhad, Iran from April 20th to December 25th, 2017. The participants were selected between 10 days to one year after childbirth. Data were collected through semi-structured interviews. Conventional content analysis approach was performed, concurrently, with data collection. To organize data, the MAXQDA 10 was used. Results: Social recovery after perineal trauma was conceptualized as 'shifting from personal ill-health to interactional empowerment'. Two generic categories emerged from data analysis including 1) impaired individual and social function, which was recognized by social isolation and lack of ability to manage daily life and 2) empowering social interactions, which was characterized by rebuilding social partnerships and returning to an interactive lifestyle. Conclusions: Social isolation as the result of neglecting social recovery of women with severe perineal trauma endangers the mental health of mothers. Understanding the concept of social recovery for women with perineal trauma, especially in severe cases, will help health professionals to provide quality postpartum care for women with perineal trauma in a longer period after childbirth.